New technique for laparoscopic partial splenectomy to decrease blood loss - Morshed, Ghada; El-Gaabary, Tamer (International Surgery Journal, 2018)
Background: Laparoscopic splenectomy is feasible, effective, and safe with low morbidity rates, faster recovery when compared with patients who undergo open splenectomy. The aim of this study was to describe a new technique for laparoscopic partial splenectomy to decrease blood loss. Methods: This study started from May 2015 till April 2017. This retrospective study included total 20 adults containing 12 females, ten with hydatid cyst of the spleen with positive serological tests for Echinococcus granulosus (Indirect hemagglutination (IHA)) was used, and two cases with congenital splenic cysts with negative serology for Echinococcus granulosus and eight males with hydatid cyst positive serological tests for Echinococcus granulosus. Results: The mean time for laparoscopic resection was 150 minutes (range from 90 to 200 min). No bleeding, no postoperative pancreatic fistula or diaphragmatic injury. No conversion was necessary. The mean hospital stay was 4 days (range from 2 to 6 days). None of the patients needed postoperative blood transfusion. No post-splenectomy infections. Three weeks and after 6 months postoperatively, US Doppler was done and found normal vascularisation of the splenic remnant. Conclusions: Clipless, Sutureless laparoscopic partial splenectomy is feasible and safe. This surgical procedure offers advantages of decrease blood loss and preservation of splenic tissue, reducing the risk of post-splenectomy sepsis.